Socio-economic futures for cellular agriculture: the development of a novel framework - Glaros, Alesandros; Newell, Robert; Fraser, Evan; Newman, Lenore Lauri (Frontiers in Sustainable Food Systems, 2023)
Novel agri-food technologies such as cellular agriculture present strong economic opportunities, with potential to reduce the environmental footprint of agriculture, improve animal welfare, and feed the world. A rich body of literature has emerged in the past five years that evaluates those claims, and illuminates the diverse food system futures framed by novel agri-food technology actors across the food system. To date, those characterizations of food system futures rely mainly on public data, such as technology advertisements and press releases, and have yet to engage deeply with a broader suite of social, economic, and material pathways for their emergence. The need for a robust social scientific framework through which to describe and evaluate concrete futures for novel food technologies such as cellular agriculture is needed. In this paper, we draw from a set of fifty-two interviews and 3 focus groups with key cellular agriculture stakeholders from industry, academia, investment, and research institutions. We found three key considerations for cellular agriculture futures: to understand the places and scales across which cellular agriculture ‘happens’, to balance competitive industry interests with public-private collaboration, and to navigate the extent to which cellular agriculture interfaces with traditional agriculture. From these considerations, we draw from the literature to deduce three dimensions across which to describe and evaluate concrete futures for novel agri-food technologies, broadly: centralization, access, and integration. Plotting food system futures across these three variables illuminates assumptions, preconceptions, and enabling conditions that may engender more or less desirable futures.